Unlocking male sterility in horticultural crops through gene editing technology for precision breeding applications: presentation of a case study in tomato - Farinati, Silvia; Soria Garcia, Adriana Fernanda; Draga, Samela; Vannozzi, Alessandro; Palumbo, Fabio; Scariolo, Francesco; Gabelli, Giovanni; Barcaccia, Gianni (Frontiers in Plant Science, 2025)
Plant male sterility (MS) refers to the failure of the production of functional anthers, viable pollen grains and/or fertile sperm cells. This feature has great potential in horticultural crops for the exploitation of heterosis through the development of F1 hybrid varieties. MS in plants can occur spontaneously or can be induced artificially by exploiting biotechnological tools, such as the editing of genes involved in spore formation or pollen development. The success of such an approach strongly depends both on preliminary knowledge of the involved genes and on effective procedures for in vitro transfection/regeneration of whole plants. Furthermore, according to previous studies based on CRISPR/Cas9 technology, the efficacy of targeting and the resulting mutation profile are critically influenced by intrinsic factors, such as the CRISPR target primary sequence sites and chromatin signatures, which are often associated with varying levels of chromatin accessibility across different genomic regions. This relationship underscores the complexity of CRISPR-based genome editing and highlights the need to identify a precise suitable target. Our paper reports the results obtained for site-specific in vivo mutagenesis via a CRISPR/Cas9-mediated strategy applied to the MYB80 gene, which is a promising target for implementing male sterility in horticultural crops. We highlight the main steps that play a key role in the whole experimental pipeline, which aims at the generation of CRISPR/Cas-edited DNA-free tomato plants. This goal was achieved via protoplast-based technology and by directly delivering a ribonucleoprotein complex consisting of the Cas9 protein and in vitro synthesized single guide RNAs that can target different positions of the gene under investigation. Overall findings and insights are presented and critically discussed.